ANALISIS PENERAPAN TATA KELOLA ADMINISTRASI PEMERINTAHAN DESA PADA DESA KARYA INDAH KECAMATAN BUNTULIA KABUPATEN POHUWATO - Edy Sijaya (Universitas Islam Darul Ulum Lamongan, 2022)
The aims of this research are: to know and to analyze the application of administrative governance of Karya Indah Village, Buntulia District, Pohuwato Regency. The method in this study is descriptive analysis, with a quantitative approach which aims to provide an overview or explanation of the Implementation of Village Administrative Governance at the Karya Indah Village Office, Buntulia District, Pohuwato Regency. In this case, the population is all village apparatus of Karya Indah consisting of village secretaries, heads of affairs, hamlet heads, totaling 13 people and BPD Desa Karya Indah members, totaling 7 people. So that the population in this study amounted to 20 people. While the sampling in this study used saturated sampling because seeing a population of less than 100, all members of the population were sampled. Thus, the number of samples in this study were 20 respondents. The results of the study show that the application of village administrative governance, in Karya Indah village, seen from the policy dimension, has been going well, this is evidenced by the knowledge of the apparatus that administrative governance policies originate from Permendagri No. 47 of 2016, besides administrative governance it is very important that its implementation is also very supported by office facilities and infrastructure. The implementation of village administrative governance, in Karya Indah village, seen from the directing dimension, has been going well. This is evidenced by the explanation of technical guidelines, apparatus also has skills because they have adequate education, apparatus is easy to obtain information and also understands the authority and duties of each. The implementation of village administrative governance, in Karya Indah village, seen from the control dimension, has also been going well. This is evidenced in addition to getting the support of adequate facilities or infrastructure, the application of administrative governance in this working village also receives financial support, and the application of administrative governance has been carried out through computerization.